Perencanaan Keuangan Untuk Mendorong Investasi Siswa SMAN 4 Depok - Ossi Ferli; Bambang Budhijana; Ajeng Rida Riyanti; Catur Nugrahani; Yola Pangestu Anggraeni; Rama Aldian Putra (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Financial planning to encourage investment in SMAN 4 Depok students is carried out so that SMAN 4 Depok students understand the concept of financial planning and investment so that students start getting to know about investment from an early age. Qualitative methods were used in this study with data obtained from pre-test and post-test questionnaires to students of SMAN 4 Depok. The result obtained by researchers after conducting socialization is an increase in students' understanding of personal financial planning and investment so that they can make wise financial decisions early. The focus of material suggestions expected by SMAN 4 Depok students is advanced material related to investment, such as more specific submissions related to investment instruments. Based on the community service activities presented and the suggestions provided by the students, there is a keen interest in delving deeper into advanced investment topics. This proves that delivering financial planning and investment material with the right approach can enhance students' financial awareness and interest.